Pengaruh Pemahaman, Kepedulian, Dan Keterlibatan Terhadap Penerapan Green Accounting Dalam Konteks University Social Responsibility - Margaretha, Florensia; Tipa, Handra (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study scrutinizes the influence of knowledge, environmental concern, and active engagement on the implementation of green accounting within the framework of University Social Responsibility (USR) across higher education institutions in Batam. Adopting a quantitative approach, empirical data were garnered through a survey targeting accounting faculty and students at Universitas Internasional Batam, Universitas Batam, and Universitas Universal. Utilizing a stratified random sampling technique, 92 respondents were recruited, with the resulting data processed via multiple linear regression analysis. The findings reveal that intellectual comprehension and active involvement serve as primary determinants that significantly drive green accounting practices. Conversely, the aspect of environmental concern, when examined partially, fails to exert a meaningful statistical impact on institutional environmental policies. Nevertheless, viewed collectively, the synergy between literacy, ecological empathy, and tangible participation emerges as a pivotal prerequisite for a successful USR system. These results underscore that the transition toward a "green campus" cannot merely rely on passive sentiments of concern; rather, it necessitates cognitive maturity and direct involvement from the entire academic community. Consequently, universities are encouraged to formulate more integrative sustainability policies, prioritizing technical education and collaborative spaces to optimize accountable environmental governance.